Ijtihad Kontemporer : Memahami Penetapan Hadis DalamHukum Jual Beli Online (As-Sahla: Journal Of Islamic Studies, 2025)
The significance of modern ijtihad in comprehending and constructing the legal framework for online purchasing and selling is discussed in this paper. The lack of explicit nash (legal texts) that explicitly govern internet transactions in the Qur'an and Hadith makes this necessary. Ijtihad turns into an essential instrument for formulating new rules that are pertinent to the dynamics of contemporary life, particularly in reaction to shifting demands. A modern economic phenomenon brought about by developments in communication and information technology, online buying and selling has replaced in-person contact in transactions. The study takes a legal and normative stance, particularly from the standpoint of fiqh muamalah. A variety of literary sources, such as books, scholarly journals, research reports, and websites, are used to compile information. Using component, taxonomic, and domain analysis, the data is presented descriptively. Product photos and comprehensive specs are usually displayed by vendors in online transactions, and buyers can get in touch with sellers to complete transactions. This transaction paradigm frequently has the consumer paying up ahead and the seller delivering the product later.